Influence of Diet Pattern on the Risk of Colorectal Cancer: A Systematic Review - Zahiro, Syayida Roisatus; Mutiah, Roihatul (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v1i0.2132, 2022)
Colorectal cancer ranks fourth in most cases in Indonesia. Diet is one of the risk factors for colorectal cancer. This study aimed to determine the effect of diet in increasing the risk of colorectal cancer and its mechanism in the progression of colorectal cancer. The method used is Preferred Reporting Items for Systematic Review Analysis (PRISMA) on the Google Scholar database, PubMed NCBI, and Science Direct. The analysis results of 23 articles that meet the criteria show that several food ingredients can increase the risk of colorectal cancer, including fat, fructose, and nitrate. Smoking and drinking alcohol also increases the risk of colorectal cancer. In contrast, vitamin D and fiber can reduce the risk of colorectal cancer. Therefore, this understanding is essential for doctors and the public to participate in reducing the incidence of colorectal cancer.